IMPLEMENTASI SEARCH ENGINE (MESIN PENCARI) MENGGUNAKAN METODE VECTOR SPACE MODEL - Fatkhul Amin (Jurnal Ilmiah Dinamika Teknik, 2011)
Growth of Machine Searcher in this time yield high recall and store; level of precision low. Recall which is high to be interpreted that document which yielded in investigation of document many, while low accuracy store level can be interpreted that expected document can be found a few/little or lower. Solution to overcome the problem of above by making meeting system return information use method of Vector Space Model (VSM). Method of VSM selected because way of model efficient, easy to in representative and earn implementation at document-matching. Keywords: Vector Space Model, Recall, Search Machine